On Rectifying Dual Space Curves - Yücesan, Ahmet; Ayyildiz, Nihat; Cöken, A. Ceylan (Revista Matemática Complutense, 2007)
We give some characterizations of the rectifying curves in the dual space and show that rectifying dual space curves can be stated with the aid of dual unit spherical curves. Thus, we have a link between rectifying dual space curves and classical surfaces in the Euclidean three-space.